2014
DOI: 10.1371/journal.pone.0088374
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Microarrays Suggest Escherichia coli ST131 Is Not a Metabolically Distinct Lineage of Extra-Intestinal Pathogenic E. coli

Abstract: Extraintestinal pathogenic E. coli (ExPEC) are the major aetiological agent of urinary tract infections (UTIs) in humans. The emergence of the CTX-M producing clone E. coli ST131 represents a major challenge to public health worldwide. A recent study on the metabolic potential of E. coli isolates demonstrated an association between the E. coli ST131 clone and enhanced utilisation of a panel of metabolic substrates. The studies presented here investigated the metabolic potential of ST131 and other major ExPEC S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
3
21
1
Order By: Relevance
“…In this connection, we tested and compared sugar source utilization and found that the ST131 strains were only moderately superior to the other E. coli strains tested in metabolizing the 35 sugars tested. Our data are not in total agreement with those of Gibreel et al (52) or Alqasim et al (49) because our study did not show either a significantly enhanced or a significantly reduced metabolic capacity of ST131 strains in comparison with the metabolic capacity of other non-ST131 E. coli strains. This discrepancy could be due to differences in the types of tests employed, differences in the study populations, and/or comparisons of biased samples.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this connection, we tested and compared sugar source utilization and found that the ST131 strains were only moderately superior to the other E. coli strains tested in metabolizing the 35 sugars tested. Our data are not in total agreement with those of Gibreel et al (52) or Alqasim et al (49) because our study did not show either a significantly enhanced or a significantly reduced metabolic capacity of ST131 strains in comparison with the metabolic capacity of other non-ST131 E. coli strains. This discrepancy could be due to differences in the types of tests employed, differences in the study populations, and/or comparisons of biased samples.…”
Section: Discussioncontrasting
confidence: 99%
“…The outcome of the zebra fish lethality assay added to our understanding that E. coli ST131 isolates possess an enhanced virulence potential and, thereby, an enhanced ability to cause invasive disease (20,46,47), although this may not consistently corroborate the findings of different studies performed in different settings and with different isolates (48)(49)(50)(51)(52). Nevertheless, the assay provided a much needed in vivo snapshot to establish the virulence attributes of our ST131 strains in adult zebra fish, even though the number of strains in each group was limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long branch lengths of the ST 131 cluster reflected ancient origins and high diversity within the ST. Consistent with our findings, a recent study using a phenotypic microarray showed that ST 131 was not a distinct lineage of ExPEC (Alqasim et al, 2014). We observed a similar level of diversity in other sequence types, with substantial variation among strains of the same ST of over 100 pairwise differences.…”
Section: Discussionsupporting
confidence: 93%
“…To increase the number of conditions available for testing, bacterial PMs have been designed to comprehensively screen bacterial strains for unique phenotypes (18). These arrays have been used to assess the fitness cost of antimicrobial resistance (19), to determine whether the increased pathogenicity of sequence type 131 extraintestinal pathogenic Escherichia coli is due to an altered metabolic profile (20), to examine the biological role of two-component systems in E. coli (21), and to identify the physiological functions of genes (22,23). Here, we have optimized growth conditions (culture medium, inoculum size, and incubation time) for N. gonorrhoeae and used them for the first PM analysis of N. gonorrhoeae to assess the physiological functions of vaccine candidate proteins NGO1205, NGO2054, NGO2121, NGO1985, NGO2054, chromosome locus J]); however, in N. gonorrhoeae, it does not contain an invariant cysteine residue, a hallmark feature of all lipoproteins (4).…”
mentioning
confidence: 99%